Bivalvia di Perairan Pantai Cermin, Kabupaten Serdang Bedagai - Nanda Mutia Hardianti; Yunasfi Djayus; Desrita Desrita (AQUACOASTMARINE, 2014)
The Cermin Beach has a higher natural value such as biodiversity, one of them is bivalve. The objective this research is to study the community structure of bivalve and waters condition in Pantai Cermin of Serdang Bedagai Regency. This research was conducted since June - August 2013 using transec method at 3 station and 4 time interval of sampling. The observed physical and chemical parameter are temperature, salinity, pH, DO, TSS, and type of basic substrate.Bivalve are found in Cermin Beach of Serdang Bedagai Regency consists 15 species, i.e. The species with most value on each station is Donax cuneatus with the abudance in station I that is 150 ind/m2, the abudance in station II that is 331 ind/m2 and abudance in station III is 247 ind/m2. The species diversity index of bivalve range from 0,85 – 1,22, uniformity index of bivalve range from 0,18 – 0,30, domination index of bivalve range from 0,35 – 0,57 and pollution index range from 1,23 – 1,61 is lightly polluted.Keywords: Bivalvia,Cermin Beach, Community Structure